Solid pseudopapillary tumor of the pancreas - Kamat Rima; Naik Leena; Joshi Rajeev; Amrapurkar Anjali; Shetty T (Wolters Kluwer Medknow Publications, 2008)
Solid pseudopapillary tumor of the pancreas is considered to be a rare pancreatic tumor. These tumors are typically present in women in their third decade of life. The tumors have a low malignant potential. We report a case of 22-year-old female who presented with intermittent abdominal pain of 3 years duration. Distal pancreatectomy with splenectomy was done as a definitive treatment. The importance of accurate diagnosis and treatment is emphasized.